Direct Cash Assistance (BLT) Strategy to Support Community Economic Resilience in Nagari Koto Tuo Lima Puluh Kota - Hilda Suryanis; Mami Nofrianti; Beni Puta Hanafi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The main problem in this thesis is how the strategy used in the Direct Cash Assistance (BLT) program implemented in Koto Tuo Village, Harau District, Lima Puluh Kota Regency, supports community economic resilience. This includes the planning, implementation, and monitoring stages of the BLT program. Furthermore, the problem also focuses on the extent to which the BLT program can improve community economic welfare and encourage empowerment for recipients, as well as the challenges faced during its implementation at the village level. qualitative approach. Qualitative research is based on honest, as-is statements, used to observe the condition of a natural object, for which this research serves as a key instrument. Data collection techniques used are triangulation (combined), data analysis contains qualitative data, and qualitative results emphasize meaning over generalization. From the fieldwork conducted by the researcher, it can be concluded that the Direct Cash Assistance (BLT) strategy in Koto Tuo Village, Harau District, Lima Puluh Kota Regency, has been implemented through planning, implementation, and monitoring stages, involving the village government and local community elements. During the planning stage, BLT recipients were determined through a special village meeting and established criteria to ensure appropriate distribution. BLT implementation followed existing regulations, although several challenges remained, such as budget limitations and beneficiary data collection. Meanwhile, oversight was carried out by the village government and relevant institutions to mitigate potential irregularities in aid distribution. The BLT program has had a positive impact on the economic resilience of recipients, particularly in meeting basic needs and reducing household economic stress. However, in terms of community empowerment, the Direct Cash Assistance (BLT) is still temporary and has not yet fully encouraged recipients' economic independence. Key challenges in implementing BLT include limited funding, inaccurate recipient data, and the dependence of some communities on aid. Therefore, a follow-up strategy is needed that combines BLT with economic empowerment programs to achieve sustainable community economic resilience.